Preparation of styrene acrylic copolymers as toner resin by suspension polymerization / Tang Bee Kim - Tang, Bee Kim (2012)
Toner resins are polymeric materials used in the manufacturing of toners to be used in the photocopy machines and LaserJet printers. The popular commercial resins are the styrene acrylic copolymers. A typical toner resin has a bimodal molecular weight distribution, having one fraction of lower molecular weight and another of higher molecular weight, so that it can impart good fixing and offset properties to provide the performance of a good toner. This research project describes the synthesis of toner resins by suspension polymerization, using poly(vinyl alcohol) and benzoyl peroxide as a colloid stabilizer and initiator respectively, in an aqueous medium to produce the copolymers in the form of tiny beads. Three series of experiments were carried in the study: (i) synthesis of low molecular weight styrene acrylic copolymers, (ii) synthesis of high molecular weight styrene acrylic copolymers and (iii) blending the both high and low molecular weight copolymers at different ratios to obtain the desired properties. Gel permeation chromatography (GPC) was used to study molecular weight distribution (MWD); melt flow index (MFI) reflected the flow ability of resin; Differential Scanning Calorimetry (DSC) was used to study the thermal properties; and acid number (AN) to quantify the amount of acidic groups in the resin. The effects of monomer ratio, concentration of initiator and concentration of crosslinking agent on the properties of high and low molecular weight resins had been investigated. The desired glass transition temperature of toner resin was obtained by varying the monomer ratio. By increasing the concentration of initiator, the number average of molecular weight of resin tends to shift to lower molecular weight presumably due to the excess free radicals that could lead to more chain termination and chain transfer reactions. The addition of cross-linking agent leads to gel formation. The percentage of tetrahydrofuran (THF) insoluble fraction has increased as the concentration of cross-linking agent was increased. The properties of synthesized toner resins were compared to those of selected commercial resins. The synthesized resins after blend at different ratios have glass transition temperature in the range of 56-69oC; MFI in the range of 13 – 55 g/10 min; AN in the range of 2.5 - 3.4 mg KOH/g; Mw in the range of 7.00 x 103 – 3.20 x 103 Daltons (1 Daltons = 1.66 x 10-27 kg) with 9 - 14% of tetrahydrofuran (THF) insoluble fraction. Three of the synthesized resins with desired properties had been tested in a lab scale production of toner. Print test had been carried out to evaluate the print quality. Image density of the test images are in the range of 1.33 - 1.58 which is comparable to commercial toner, while background density is around 0.12-0.13 which is slightly higher than commercial toner.